NEW PRINCIPLES OF FORMATION AND REALIZATION OF THE INVESTMENT PROGRAM OF RAILWAYS - Levytskyi, I. Ye. (Science and Transport Progress, 2007)
A new approach to implementation of investment projects on the railway transport is proposed in this paper, as well as the options of increasing efficiency of the projects.